Revisiting the typification of Ranunculus cantoniensis (Ranunculaceae) and some of its synonyms - Mukhopadhyay, S.; Roy, B. (Rheedea, 2025)
The perplexities of nomenclature warrant the addressal of the typification of Ranunculus cantoniensis and some of its synonyms include R. fibrosus and R. napaulensis. The present paper designates the neotype for R. cantoniensis and lectotype for R. fibrosus. The holotype of R. napaulensis is found in G instead of K, and we also discuss the correction of orthographic errors of this name that have crept into relevant literature.